2011
DOI: 10.1093/toxsci/kfr007
|View full text |Cite
|
Sign up to set email alerts
|

Embryoprotective Role of Endogenous Catalase in Acatalasemic and Human Catalase-Expressing Mouse Embryos Exposed in Culture to Developmental and Phenytoin-Enhanced Oxidative Stress

Abstract: Reactive oxygen species (ROS) are implicated in spontaneous and xenobiotic-enhanced embryopathies, and protein therapy with exogenous catalase suggests an embryoprotective role, although embryonic catalase activity is only about 5% of adult activity. Using mutant catalase-deficient (acatalasemic, aCat) mice and transgenic mice expressing human catalase (hCat, enhanced catalase activity) compared with a confirmed outbred CD-1 mouse model, we investigated the protective importance of constitutive embryonic catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…The results for fetal exposure extend the gestational range of importance covered in recent studies showing a protective role for endogenous catalase in the same genetically altered models during organogenesis in embryo culture [23] and in vivo [22], which revealed structural rather than functional consequences of in utero developmental and phenytoin-enhanced oxidative stress.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The results for fetal exposure extend the gestational range of importance covered in recent studies showing a protective role for endogenous catalase in the same genetically altered models during organogenesis in embryo culture [23] and in vivo [22], which revealed structural rather than functional consequences of in utero developmental and phenytoin-enhanced oxidative stress.…”
Section: Discussionsupporting
confidence: 76%
“…Individual pups rather than litters were used as the experimental unit in the primary analysis because the teratogenicity of phenytoin depends at least in part on its bioactivation to a reactive intermediate, and risk depends upon fetal rather than maternal determinants of drug bioactivation and ROS formation, reactive intermediate and ROS detoxification, and possibly DNA repair [17]. We also have previously shown that the level of catalase in individual embryos correlates with their own developmental outcome, independent of the dam [23].…”
Section: Preweaning Functional Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…at ASPET Journals on May 9, 2018 molpharm.aspetjournals.org ticularly susceptible to damage by hydrogen peroxide (Abramov and Wells, 2011). Of interest, the same study also demonstrated in embryos cultured with the ROS-initiating teratogen phenytoin that embryos with failed anterior neuropore closure and embryos that failed to turn have significantly decreased levels of catalase activity compared with those in embryos that developed normally.…”
Section: Tung and Winnmentioning
confidence: 78%